Selected International Aspects of Carbon Taxation - McLure, Charles E. (American Economic Review, 2014)
Disparate commitments to reduce GHG emissions create demands for border carbon adjustments (BCAs) to prevent negative competitive effects and carbon leakage. BCAs that accomplish economic objectives and are administratively feasible, WTO-legal, and politically acceptable may be impossible. BCAs should be limited to a few basic energy-intensive and trade-exposed products and should be based on the lower of the carbon content of production in the importing country and actual carbon content, or perhaps “best available technology.” Whether the World Trade Organization (WTO) would condone BCAs is unclear. BCAs violating basic trade rules might qualify for a special exception.